PENGEMBANGAN SISTEM REKRUTMEN LOWONGAN KERJA BERBASIS WEB UNTUK OPTIMALISASI BURSA KERJA KHUSUS (BKK) - Daniati Uki Eka Saputri; Sardiarinto Sardiarinto (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
Bursa Kerja Khusus (BKK) at Vocational High Schools (SMK) plays a crucial role in connecting graduates with the workforce. However, the current manual process of disseminating job vacancies and handling applications leads to suboptimal information distribution and inefficient data management. This study aims to design and develop a web-based job recruitment system to improve the efficiency of information dissemination and the job application process for students and alumni of SMK Negeri 1 Ngawen. The system is developed using the Waterfall model, which includes the phases of requirements analysis, system design, implementation, testing, and maintenance. The results show that the developed system successfully delivers real-time job vacancy information, accelerates the application process, and improves the accuracy of matching candidates with available jobs. Testing conducted using the Black-Box Testing method confirms that the system functions as expected, ensuring proper input validation, secure access control, and high data integrity. It is expected that this system will enhance the employability of SMK graduates and make the recruitment process more efficient and effective.